ANALISIS DOSIS PAPARAN RADIASI DI UNIT RADIOLOGI RS. BHAYANGKARA MAKASSAR - Hasmawati, Hasmawati; Sahara, Sahara; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2016)
This study aims to measure the wall thickness of material radiation shield by using calipers, stage of measuring the radiation dose produced the best x-rays in different directions by using Surveymeter at the distance measuring point on the wall with a height of 10 cm, 1m, 2m, the third stage is measuring the radiation dose x-rays in the vertical and horizontal measurement with the object and without an object with a fixed voltage 75 Kv with distance measurements from a source to a device 1 meter and 2 meters in space and outside space. And the last stage takes raw radiation doses received by workers of the head of the installation space radiology Bhayangkara Makassar. Based on the research results in the first phase of the thick walls of the radiology that is 15 cm+2 mm (Pb) each side and wooden doors 5 cm+2 mm (Pb) and glass Pb 2 cm+2 mm (Pb), rate of radiation exposure resulting air x-ray in many directions obtained radiation is greatest there is in the direction of the left side air that is 3600 Î¼Sv/h, the dose rate on the measurement of vertical and horizontal with a specified distance of radiation of the total of the door operator vertical measurement that is equal to 3400 Î¼Sv/h, the dose received by the operator of the largest radiation received by the third receiver that is equal to 0.1599 Î¼Sv / h and the measurement results outside the room is 0.00 Î¼Sv / h was not detected while the radiation received by the receiver the first small at 0.1546 Î¼Sv/h and the mean dose average received by the operator of 0.1 Î¼Sv/h this is in accordance with the SNI allowed for workers is 50 mSv/ h in the first year.Â Keywords : radiation dose , radiation workers , radiation shield